La présence de la littérature française renaissante dans les catalogues des ventes aux enchères en Hollande au XVIIe siècle. Bilan et perspectives - Smith, Paul J. (Renaissance and Reformation / Renaissance et Réforme, 2011)
How does one gauge the reception of French Renaissance authors in the Netherlands? Auction catalogues from private libraries are certainly the most useful tools for this endeavour, and we have knowledge of them thanks to studies by many scholars. The project Book Sales Catalogues of the Dutch Republic—by the Royal Library of The Hague and of the University of Leiden—made available to researchers a large corpus of sales catalogues from the seventeenth and eighteenth centuries. Currently, the microfilm is being digitized by Brill editions and will soon be available on the Internet. After having studied the Dutch reception of Marot, Rabelais, Montaigne, Du Bartas, Desportes and Molière, the author of this article proposes the synthetic review of this approach for the study of literary reception. The author evaluates the material and methodological problems, the established knowledge and new perspectives, focusing on the importance of these catalogues to both contemporary and modern bibliographical practice. The present article treats mainly sales catalogues from private libraries, saving sales catalogues of bookstore stock, printers’ stock, and other assorted bookseller catalogues for another study.